PENGARUH PENGGUNAAN MODUL PADA MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN KETERAMPILAN KOMPUTER DAN PENGELOLAAN INFORMASI DI SMK NEGERI 2 BUKITTINGGI - Febrina Aulia; Zulhendra Zulhendra; Putra Jaya (Universitas Negeri Padang, 2014)
This research is aimed to know how big use of learning module affect studentslearning outcome in Keterampilan Komputer dan Pengelolaan Informasi study forgrade XI of SMK Negeri 2 Bukittinggi in academic year 2013/2014. This type ofresearch is experimental research pretest pottest control group design.Population is students grade XI of SMKN 2 Bukittinggi. Sample were selectedusing purposive sampling technique. Students from class XI PKA 3 which chosenas experiment class, used cooperative learning with learning module. Studentsfrom class XI PKP 1, which served as control class, used cooperative learningwithout learning module. Data were obtained using achievement test in the formof multiple choice questions with 25 items of questions. The result of analysisshowed that experiment class mean of learning outcome 89,23 and control class79,41. Effect of using learning module toward learning outcome is 12,4%. Theresult of analysis showed that t-obtained was 6.812 at significance level α = 0.05and degrees of freedom = n - 1 , while t-table was 1.699. So t-obtained is greaterthan t table (6.812 > 1.699 ) and p=0,000. P value smaller than 0,05 so H0rejected and Ha accepted. Based on result can be concluded that using learningmodule give significant effect toward students learning outcomes.